Penyerangan Mongol Terhadap Dinasti Abbasiyah Dan Dampaknya Pada Peradaban Islam Serta Bidang Sosial-Politik Tahun 1258 M - Miftahul Jannatil Harvina; Nicky Bima Koni Ramadhan; Ellya Roza (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2025)
The Mongol invasion in 1258 AD brought an end to the glory of the Abbasid Dynasty, which for centuries had been the political and intellectual center of Islam. This event not only toppled Baghdad as the epicenter of civilization but also shook the social and political order of the Islamic world. This research employs the library research method by examining and analyzing various primary and secondary sources discussing the history of the Mongol invasion. The analysis is carried out through a qualitative approach using content analysis to explore the impact of the event on Islamic civilization in its political aspect. Based on the findings, although the city of Baghdad suffered severe destruction as a result of Hulagu Khan’s invasion in 1258 AD which simultaneously marked the end of the central authority of the Abbasid Dynasty, the event in fact became a catalyst for major transformation in the history of the Islamic world. The Mongol assault, which initially brought devastation, paradoxically opened the way for a new phase of revival. The Ilkhanate Dynasty, which at first posed a threat to Muslims, eventually embraced Islam and played a strategic role in rebuilding political stability in the previously ravaged regions. This included the implementation of the jizyah tax on non-Muslims, the prohibition of usury, and the obligation for officials to wear turbans as an Islamic identity marker.